The state of export and import of wood products and furniture in the Republic of North Macedonia: Trends and strategies for growth - Stamenkoska, Ana-marija; Meloska, ZHivka; Meloska, Angelina; Petrovska, Ilijana; Antovska, Ivana; Temelkova, Anastasija (WoodEMA, i.a. – International Association for Economics and Management in Wood Processing and Furniture Manufacturing, 2025)
The Republic of North Macedonia has a long-standing tradition in the production and international trade of wood products and furniture. This paper presents an analysis of the dynamics of wood and furniture import and export during the period from 2014 to 2023, based on data obtained from the Economic Chamber and the State Statistical Office of the Republic of North Macedonia. The data were classified according to the Standard International Trade Classification (SITC). The results reveal a notable upward trend in exports — nearly five times for furniture and three times for wood products. A similar increasing trend is observed across all categories of imports. The aim of this study is to provide a comprehensive assessment of external trade trends in the wood and furniture sector, with the objective of formulating strategic directions for enhancing export growth and market competitiveness.
Keywords: import; export; wood; wood products; furniture